Manipulation of the endocytic pathway and phagocyte functions by Mycobacterium tuberculosis lipoarabinomannan - Vergne, Isabelle; Gilleron, Martine; Nigou, Jérôme (Frontiers in Cellular and Infection Microbiology, 2015)
Lipoarabinomannan is a major immunomodulatory lipoglycan found in the cell envelope of Mycobacterium tuberculosis and related human pathogens. It reproduces several salient properties of M. tuberculosis in phagocytic cells, including inhibition of pro-inflammatory cytokine production, inhibition of phagolysosome biogenesis and inhibition of apoptosis as well as autophagy. In this review, we present our current knowledge on lipoarabinomannan structure and ability to manipulate the endocytic pathway as well as phagocyte functions. A special focus is put on the molecular mechanisms employed and the signaling pathways hijacked. Available information is discussed in the context of M. tuberculosis pathogenesis.